Kidney abnormality detection and classification using ultrasound vector graphic image analysis [electronic resource] - Wan Mahani Hafizah Wan Mahmud, 1987- (2013)
Thesis (Ph.D (Kejuruteraan Bioperubatan)) - Universiti Teknologi Malaysia, 2013